Nghiên cứu phân tích các tài sản trú ẩn an toàn đối với thị trường cổ phiếu Việt Nam - Đặng Phong, Nguyên; Đặng Thị Việt, Đức; Đỗ Hoài, Linh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study investigates the safe haven properties of several typical financial assets against the Vietnamese stock market during the 2020–2025 period, examining two distinct sub-periods: the COVID-19 pandemic and the periods of global geopolitical tensions. Using an OLS regression model with nearly 1,400 observations, the authors analyze fluctuations across four asset classes: Commodities, government bonds, foreign currencies, and cryptocurrencies, during periods of sharp declines in the Vietnamese market. The findings indicate that in a frontier market such as Vietnam, gold does not exhibit safe haven characteristics. Conversely, government bonds and the USD demonstrate strong safe-haven properties against the Vietnamese stock market. Most of the remaining assets fail to provide safe havens, acting only as weak hedges.
Keywords: Vietnam; Hedge; Safe haven; Stocks